2009
DOI: 10.1007/s10530-009-9441-4
|View full text |Cite
|
Sign up to set email alerts
|

Flooding compromises compensatory capacity of an invasive plant: implications for biological control

Abstract: Plant compensatory growth is proposed to be insidious to biological control and known to vary under different environmental conditions. However, the effects of microsite conditions on compensation capacity and its indirect impacts on biological control of plant invaders have received little attention. Alligator weed, Alternanthera phioxeroides, is an invasive plant worldwide, growing in both aquatic and terrestrial habitats that are often affected by flooding. Biological control insects have been successful in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 43 publications
1
21
1
Order By: Relevance
“…This survey found that the plant range was from 20°N to 34.7°N and its population size was greatest in regions between 30°N and 32.5°N. Previous studies in China found that the beetle has only successfully suppressed A. philoxeroides in aquatic habitats but has limited impact in terrestrial habitats , partly due to lower pupal survival (Ma & Wang, ) and high plant tolerance of herbivory (Lu & Ding, ). Consequently, the terrestrial form of A. philoxeroides is still very invasive in China.…”
Section: Introductionmentioning
confidence: 98%
“…This survey found that the plant range was from 20°N to 34.7°N and its population size was greatest in regions between 30°N and 32.5°N. Previous studies in China found that the beetle has only successfully suppressed A. philoxeroides in aquatic habitats but has limited impact in terrestrial habitats , partly due to lower pupal survival (Ma & Wang, ) and high plant tolerance of herbivory (Lu & Ding, ). Consequently, the terrestrial form of A. philoxeroides is still very invasive in China.…”
Section: Introductionmentioning
confidence: 98%
“…The root morphology and distribution determine a plant's resource acquisition, especially in environments that are characterized by low water and nutrient availability (Lynch ). The root‐to‐shoot mass ratio of A. philoxeroides is lower and the roots are composed mainly of thin roots in aquatic habitats, while the root‐to‐shoot mass ratio is much higher and the roots are composed mainly of thick storage roots in terrestrial habitats (Lu & Ding ). Therefore, the level of root resource acquisition of A. philoxeroides might be lower in aquatic than terrestrial habitats, implying that the plant will perform poorly when flooded.…”
Section: Discussionmentioning
confidence: 99%
“…). In terrestrial habitats, although it can establish populations and cause damage to the weed, it has had little or no impact on the weed population due to low pupal survival (Ma & Wang ) and the high tolerance of A. philoxeroides to herbivory (Lu & Ding ). As a result, terrestrial A. philoxeroides is still invasive in China.…”
mentioning
confidence: 99%
“…[2]. Given that compensatory growth in weeds can negate the effects of biological control agents [9], this study illustrates a mechanism and growth variables that need to be measured to predict compensatory responses in weed species as a function of environmental resource levels.…”
Section: Predicting Compensatory Growth and Reproduction In Agricultumentioning
confidence: 97%